Mental Health in Self-Quarantined Pregnant Women for 14 Days During the Coronavirus Outbreak in Iran - Nasrin Ghiasi; Robab Kazempour; Arezoo Haseli; Mohammad Reza Kaffashian; Shayesteh Jahanfar (Wolters Kluwer Medknow Publications, 2024)
Background: Quarantine during COVID-19 disease may be associated with psychological distress and other behavioral problems. This study aimed to investigate depression, anxiety, and stress in self-quarantined pregnant women at home for 14 days during the coronavirus disease outbreak in Iran. Materials and Methods: A cross-sectional web survey was carried out on 874 pregnant women in all governmental health centers of two cities in Iran using the census method in 2020-21. Survey data were collected with the Depression, Anxiety, and Stress Scale-21. Data were analyzed using descriptive statistics and analytical tests (Chi-square, Pearson's correlation coefficient, and logistic regression) at significance level less than 0.05. Results: Approximately 40.04% (N = 350) of the participants were classified as a self-quarantine group. The mean (SD) of the stress score was higher for the quarantine group compared to nonquarantine (8.12 (4.95) vs. 5.96 (4.51)) (F2,874 = 25.180, p < 0.001). But there was no significant difference in the depression and anxiety scores between the quarantine group compared to nonquarantine, respectively. Additionally, the adjusted odds ratio for stress score was associated with an unwanted pregnancy (1.993, 95% CI: 1.108-3.587; p = 0.021), younger age (1.707, 95% CI: 1.082-2.692; p = 0.022) and uninsured coverage (2.240, 95% CI: 1.320-3.801; p = 0.003), and complete quarantine (2.027, 95% CI: 1.548-2.654; p < 0.001). Conclusions: Self-quarantine during the COVID-19 pandemic has been related to high-stress levels, specifically, among women of younger age, uninsured, and unwanted pregnancies. Thus, quarantined pregnant women will need more mental health support and medical supplies.